Peningkatan Kemampuan Berpikir Kritis Materi Nilai-Nilai Pancasila Melalui Pembelajaran PBL Kelas V SDN Mojorayung 01 - Dea Sindy Ramadhani; Asri Musandi; Sri Lestari (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to improve students' skills in the realm of critical thinking by learning Problem Based Learning material about Pancasila values ​​for class V students at SDN Mojorayung 01. This development research is based on an analysis of the problems found at the school in accordance with the school's needs. obtained from practical activities that have been carried out in order to gain a more comprehensive understanding. Problem Based Learning is a learning model that is based on a real problem that is used for learning and encourages students to solve problems, think critically, systematically and logically in gaining knowledge. Critical thinking skills require habits that are practiced in learning activities. These habits are built through the learning media used in learning activities. This is because critical thinking skills do not occur naturally but require habituation through classroom learning.